Comparison of dentinal hydraulic conductance according to the application time of oxalate-based desensitizers - Fernández, Eduardo; Romero, María de los Ángeles; Bersezio, Cristian; Vildósola, Patricio|; Letelier, Claudia; Oliveira-Junior, Osmil Batista; Martín, Javier (Revista Facultad de Odontología Universidad de Antioquia, 2015)
Introduction: an in vitro model was used to measure the hydraulic conductance in human dentin discs treated with oxalic acid for 15, 30 or 60 s maintaining the occlusive effect and measuring 7 and 14 days after application. Methods: 45 dentin discs measuring 1 mm thick were obtained from human third molars which were free of caries and in no occlusion; the samples were obtained from patients aged 16 to 30 years. Discs were sorted out into three study groups (n = 15) depending on the time of application of a commercial solution of oxalate-based dentin desensitizer (DD) (BisBlock®) which contains ˂ 5% oxalic acid of 1.5-1.8 pH: in group A the agent was applied for 15 s, in group B it was applied for 30 s, and in group C for 60 s. The hydraulic conductance of each disc was calculated after acid etching, which corresponds to the maximum permeability of discs (100%) after immediate application of oxalic acid, as well as seven and fourteen days of storage in saline solution. The statistical analysis was done with ANOVA test and post-hoc Games-Howell test. Results: 35,46 ± 23.41% in Group A, 36.34 ± 15.88% in Group B and 24.99 ± 14.99% in Group C, showing that the use of DD for 15, 30 or 60 s decreased permeability in a statistically significant manner (p <0.05). Conclusions: DD was effective in reducing hydraulic conductance regardless of application time, but this reduction was temporary only, since after seven days permeability returns to values close to those of baseline.